2007
DOI: 10.1577/a06-056.1
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Toxicity of Praziquantel to Grass Carp and Golden Shiners

Abstract: The acute toxicity and highest nonlethal concentration of praziquantel (LC0) were determined in the laboratory for grass carp Ctenopharyngodon idella and golden shiner Notemigonus crysoleucas, two cyprinids known to harbor the Asian tapeworm Bothriocephalus acheilognathi. Praziquantel is an anthelmintic used to treat fish with tapeworms. The 24‐h and 96‐h LC50 values were 55.1 and 49.7 mg/L for golden shiners (1.3 g) and 63.4 and 60.6 mg/L for grass carp (9.1 g). The 24‐h and 96‐h LC0 values were 50.0 and 45.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Of particular concern is the wide dose range seen with fenbendazole, as there are increasing reports of fenbendazole toxicity, including toxicity in sharks at 25 mg/kg orally. 20,21 Oral medications should be dosed based on estimated food intake and available pharmacokinetic and efficacy data. 11 Antibacterial nitrofurans were used by 25% of institutions immediately post-transport.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular concern is the wide dose range seen with fenbendazole, as there are increasing reports of fenbendazole toxicity, including toxicity in sharks at 25 mg/kg orally. 20,21 Oral medications should be dosed based on estimated food intake and available pharmacokinetic and efficacy data. 11 Antibacterial nitrofurans were used by 25% of institutions immediately post-transport.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information available on toxicity of praziquantel on fish (Mitchell & Hobbs 2007). The result regarding a possible tumour induction from praziquantel in this study could however be biased, because praziquantel was the only medication used against Gyrodactylus sp.…”
Section: Influence Of Medicationmentioning
confidence: 99%
“…Frohberg (1984) described extensive mammalian PZQ toxicity and safety studies, but these are irrelevant for understanding the safety of PZQ for fish. Mitchell and Hobbs (2007) found that the 24-and 96-h LC50 values for PZQ for juvenile golden shiners [Notemigonus crysoleucas (Mitchill 1814)] were 50.0 and 45.0 mg l -1 , and for grass carp, these were 60.0 and 60.0 mg l -1 . Obiekezie and Okafor (2008) found that the 24-h LC50 of PZQ for Clarias gariepinus (Burchell 1822) was 13.4 mg l -1 .…”
Section: Introductionmentioning
confidence: 99%